2010
DOI: 10.2465/jmps.090201
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of polymetallic mineralized pegmatite of Ras Baroud granite, Central Eastern Desert, Egypt

Abstract: An economically important rare -metal mineralization is recorded in the pegmatite bodies of Gabal Ras Baroud younger granitic pluton, Central Eastern Desert of Egypt. These pegmatite bodies are of variable size and are compositionally zoned. Radiometric measurements of some anomalous pegmatite samples show that their equivalent uranium (eU) content is 219 -328 ppm, whereas their equivalent thorium (eTh) content is 783 -1101 ppm. On the other hand, the analysis of several separated mineral grains of some pegmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Radioactive pegmatites have been recorded in many localities in the Eastern Desert of Egypt (Sayyah et al, 1993;Ibrahim et al, 1997;Ali, 2001;Ibrahim et al, 2001;Ali et al, 2005;Abdel Warith et al, 2007;Raslan et al, 2010). Also, several studies worldwide have revealed the presence of granite-pegmatite-hosted rare-metal mineralizations (Matsubara et al, 1995;Hanson et al, 1998;Erict, 2005;William et al, 2006;Pal et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Radioactive pegmatites have been recorded in many localities in the Eastern Desert of Egypt (Sayyah et al, 1993;Ibrahim et al, 1997;Ali, 2001;Ibrahim et al, 2001;Ali et al, 2005;Abdel Warith et al, 2007;Raslan et al, 2010). Also, several studies worldwide have revealed the presence of granite-pegmatite-hosted rare-metal mineralizations (Matsubara et al, 1995;Hanson et al, 1998;Erict, 2005;William et al, 2006;Pal et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…The average composition of the analyzed thorite ( The studied thorite is sporadic in U distribution, suggesting non-uniform redistributions of UO 2 within thorite during post magmatic processes. Several authors reported the presence of thorite inclusions in rare metal mineralization and accessory heavy minerals separated from some Egyptian pegmatites (Raslan et al, 2010;Ali et al, 2005;Abdel Warith et al, 2007).…”
Section: Zircon-thorite Associationmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, they added the cryptically zoned columbite crystals with Fe-rich rims suggest remarkable reducing conditions during the columbite crystallization which is also responsible for the formation of minute pyrite crystals found in the peripheral zone. Raslan et al (2010) identified samarskite-Y, columbite and zircon from pegmatite bodies and the stream sediments surrounding Ras Baroud granitic pluton. They studied the rare metals within pegmatites at G. Ras Baroud and clarify the importance of these pegmatites as hosts of accessory minerals of rare metals, REEs and radioactive elements.…”
Section: Introductionmentioning
confidence: 99%
“…Several Nb-Ta occurrences have been recorded in different localities of the Eastern Desert, namely, El Naga, Abu Khurg, Abu Dabbab, Noweibi, and Abu Rushied (HussEin, 1990;raslan & ali, 2011). It is interesting in this regard to mention that author identified Samarskite-Y, columbite and zircon from Ras Baroud granite -pegmatite in the Central Eastern Desert (raslan et al, 2010) and in the stream sediments surrounding the Ras Baroud granitic pluton (raslan, 2009).…”
Section: Introductionmentioning
confidence: 99%